Developing a Scale for Intuitive Decision-Making Styles: Enhancing Measurement of Deliberation, Heuristics, Unconscious Thought, Emotions, and Anticipation - Markus A. Launer; Frithiof Svenson (International Journal of Business and Economic Affairs, 2025)
Intuitive Decision-Making is a multi-dimensional, complex phenomenon that has to be researched in an interdisciplinary approach. Most studies have a dual approach – deliberation or intuition – others already distinct two or three different types of intuition. Latest research reveals however, intuition needs a multi-dimensional approach. The target of this study is to better describe intuition in four different styles of intuitive decision-making based on the preferences by participants from different cultures – describing a multicultural measurement instrument. This is important because most studies on scale development were done on a national level. The study aims to improve business and economic theory by describing intuition in an approach usable for various types of jobs in different industries. Therefore, the study is conducted across a sample of people from different cultures, over 30 countries, and over 35 different industries and various different job types. In the first step, the authors confirmed the measurement tool for Preference for Intuition & Deliberation (PID) in the multi-cultural sample, shortened the items catalogue, and made the items understandable in different cultures. Second, the authors improved the different styles of intuition by using adapted and new items. The cognitive decision-making style was shortened to three items, making it very usable for further studies. The dimension experienced-based intuition was better described based on the heuristic theory. The intuition style affective emotional was divided into two separate dimensions, describing the item hunches in more detail, now named: Anticipation. The newly proposed intuition style is Unconscious Thoughts which are not measured in the former studies. This analysis is based on the findings of a European Union funded project called RHIA, which used a self-rated scale to ask 5574 employees about their preferences at work. After using established testing approaches, like Exploratory Factor Analysis (EFA), a Confirmatory Factor Analysis (CFA), the Cronbach’s Alpha coefficients, as well as the Primary Component Analysis (PCA), Maximum Reliability (Hancock‘s H), and Classical Test Theory, the results presented are robust, valid and reliable new and improved intuition decision-making styles for the use in measurement instruments and practice.